Comparison of Translation Quality between Google Translate, SDL Free Translation and Tradukka in the Health Article Entitled `Vaginal Birth After Caesarean` - Ika Oktaria Cahyaningrum; Yunita Widiyantari (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
The purpose of this research is to find out the comparison of translation quality produced at online translation of Google Translate, SDL Free Translation and Tradukka. In consequence with the existence of this research, is expected to give positive contribution to the users of online translation services in particular and translation researchers generally in providing information about the quality of translation produced. Google Translate, SDL Free Translation and Tradukka both have pages that are quite simple but have different levels of translation quality. Thus research is to compare between Google Translate as one of the sites that often opened and produced translation quality more accurate, acceptable and has a high level of readability with two other sites. In addition, there is still much doubt about the quality of a translation machine in producing translations of quality.